1982
DOI: 10.1111/j.1600-0536.1982.tb04151.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of contact allergy and hand eczemas in hospital wet work

Abstract: The occurrence of contact sensitivity and hand dermatitis was studied in hospital employees. The incidence of contact allergy was 21%. Nickel (9%) was the most common allergen followed by perfumes (6%). Present of previous hand dermatitis was detected in 46%. Of those with positive reactions, 53% had suffered from hand dermatitis as compared to 44% of those without positive reactions. 70% of those with sensitivity to fragrances had suffered from hand dermatitis. The occurrence of hand dermatitis was more frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…Romaguera et al (1985) reported positive reactions in 11 of 1023 children tested, a nearly identical prevalence rate of 1.1%, while Tunnessen (1984) reported a similar prevalence rate of 2.4%. These response rates for chromium sensitivity in children compare closely with the 1.3% prevalence rate reported by Lammintausta et al (1982) for 536 adult hospital employees. It should also be noted that these prevalence rates apply only to pédiatrie dermatology patients; the prevalence rate for chromium sensitivity in the general pédiatrie population is not known with certainty, but it may be inferred from these data that it is significantly less than 1%.…”
Section: Chromium Sensitivity In Childrensupporting
confidence: 79%
See 2 more Smart Citations
“…Romaguera et al (1985) reported positive reactions in 11 of 1023 children tested, a nearly identical prevalence rate of 1.1%, while Tunnessen (1984) reported a similar prevalence rate of 2.4%. These response rates for chromium sensitivity in children compare closely with the 1.3% prevalence rate reported by Lammintausta et al (1982) for 536 adult hospital employees. It should also be noted that these prevalence rates apply only to pédiatrie dermatology patients; the prevalence rate for chromium sensitivity in the general pédiatrie population is not known with certainty, but it may be inferred from these data that it is significantly less than 1%.…”
Section: Chromium Sensitivity In Childrensupporting
confidence: 79%
“…This is thought to be a result of the fact that chromium must first dissolve in sweat or some other liquid before it can be absorbed through the skin. Less than 3% of workers exposed to dry cement Jaeger and Pelloni, 1950Pirila, 1954Avnstorp, 1989Avnstorp, 1989Avnstorp, 1991Engebrigsten, 1952Korallus, 1974Rudzki et al, 1989Lee and Coh, 1988Hjerpe, 1986Lammintausta et al, 1982Winston and Walsh, 1951Rudski et al, 1989Peltonen and Fräki, 1983 dust have been sensitized to chromium (Avnstorp, 1989;Engebrigtsen, 1952).…”
Section: Occupational Experience With Hexavalent Chromiummentioning
confidence: 95%
See 1 more Smart Citation
“…Nursing activities can cause hand dermatitis in many ways [3,4,6,[9][10][11][12][13][14][15][17][18][19][20][21][22][23][24][25][26]. The main risk factor for developing hand dermatitis in nursing activities lies in the exposure to agents that are weakly toxic to the skin (irritants), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, some studies have described occupational allergy in hospital employees [1][2][3][4][5] . Contact dermatitis of the hands was the major occupational skin disease among occupational allergies in these employees.…”
mentioning
confidence: 99%